A Functional Assay Suggests that Heterodimers Exist in Two C-Terminal γ-Chain Dysfibrinogens: Matsumoto I and Vlissingen/Frankfurt IV - Hogan, Kelly A.; Lord, Susan T.; Okumura, Nobuo; Terasawa, Fumiko; Galanakis, Dennis K.; Scharrer, Inge; Gorkun, Oleg V. (Thrombosis and Haemostasis, 2000)
Because it contains three pairs of polypeptides, fibrinogen isolated from heterozygous individuals is expected to be a mixture of homodimers and heterodimers. Nevertheless, heterozygous individuals with only homodimers have been identified. We synthesized two recombinant fibrinogens with the mutations from fibrinogen Vlissingen/ Frankfurt IV (γΔ319, 320) and Matsumoto I (γD364H), both identified in heterozygous individuals. We found that polymerization of these fibrinogens was undetectable in 30 min; polymerization of a 1:1 mixture of variant and normal fibrinogen was the same as polymerization of a 1:1 mixture of buffer and normal fibrinogen; polymerization of either plasma fibrinogen was markedly impaired when compared to the 1:1 mixture of the respective variant and normal fibrinogens. We conclude that each plasma fibrinogen is a mix of homodimers and heterodimers, such that the incorporation of heterodimers into the fibrin clot impairs polymerization. We suggest that incorporation of heterodimers can induce clinical symptoms.
Keywords: Fibrinogen; heterodimers; polymerization